2016
DOI: 10.1021/acschembio.6b01037
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Chagas Disease Drug Target Discovery Using Directed Evolution in Drug-Sensitive Yeast

Abstract: Recent advances in cell-based, high-throughput phenotypic screening have identified new chemical compounds that are active against eukaryotic pathogens. A challenge to their future development lies in identifying these compounds’ molecular targets and binding modes. In particular, subsequent structure-based chemical optimization and target-based screening require a detailed understanding of the binding event. Here we use directed evolution and whole-genome sequencing of a drug-sensitive S. cerevisiae strain to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 71 publications
3
23
0
Order By: Relevance
“…For target identification, we first used in vitro evolution studies in the model system Saccharomyces cerevisiae, a strategy that has been used to discover the target of cladosporin, a tRNA synthetase inhibitor that acts against both P. falciparum and S. cerevisiae. We have recently demonstrated that yeast can be successfully used for drug target identification in both antimalarial and antitrypanosomal compounds [28][29][30] , so we decided to perform selections with GNF179. IZPs are moderately active (45 μM) against an attenuated strain of Saccharomyces that has been genetically modified by replacing 16 ABC multi-drug transporter genes with modified Aequorea victoria GFP (eGFP) and that has been dubbed the "Green Monster" 31 .…”
Section: Resultsmentioning
confidence: 99%
“…For target identification, we first used in vitro evolution studies in the model system Saccharomyces cerevisiae, a strategy that has been used to discover the target of cladosporin, a tRNA synthetase inhibitor that acts against both P. falciparum and S. cerevisiae. We have recently demonstrated that yeast can be successfully used for drug target identification in both antimalarial and antitrypanosomal compounds [28][29][30] , so we decided to perform selections with GNF179. IZPs are moderately active (45 μM) against an attenuated strain of Saccharomyces that has been genetically modified by replacing 16 ABC multi-drug transporter genes with modified Aequorea victoria GFP (eGFP) and that has been dubbed the "Green Monster" 31 .…”
Section: Resultsmentioning
confidence: 99%
“…This species, or collection of species, co-migrated with the ergosterol standard. However, T. cruzi amastigotes reportedly do not generate canonical ergosterol as the final species from endogenous sterol synthesis (Gunatilleke et al, 2012; Liendo et al, 1999; Ottilie et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As expected, carbons from exogenous 13 C-glutamine were readily incorporated into species downstream of CYP51 (Figure 3B). In the presence of ketoconazole, when CYP51 is inhibited, these downstream species were absent, and 13 C was incorporated into lanosterol and ebericol (Figure 3B,C), the two species immediately upstream of CYP51 in the sterol synthesis pathway (Gunatilleke et al, 2012; Ottilie et al, 2017). Unlike endogenous sterols and synthesis intermediates derived from amastigote metabolism, we did not identify any incorporation of 13 C-glutamine into host derived, but amastigote-associated, cholesterol (Figure 3B,C).…”
Section: Resultsmentioning
confidence: 99%
“…CRISPR- Cas 9 genome engineering was performed on the S. cerevisiae ABC 16 -Monster strain using vectors p414 and p426 obtained from the Church lab (Addgene) as previously described 72 . To produce gRNA plasmids specific to the desired mutation sites, oligonucleotides were synthesized (Integrated DNA Technologies) to match the target sequence and contain a 24 base-pair overlap with the p426 vector backbone.…”
Section: Methodsmentioning
confidence: 99%